Vitamin C an Update on Current Uses and Functions - Guy LeBlanc, Jean (IntechOpen, 2019)
Vitamin C, or ascorbic acid, is mainly present in fruits and vegetables. The consumption of such foods is important since the human body does not have the ability to produce this essential micronutrient. Because it is water soluble, it can also easily be lost in cooking and long-term storage. Even though the role of vitamin C has been known since the early 1930s, only recently have researchers been actively studying and demonstrating its role and function in the treatment and prevention of many diseases. These studies will be the key to providing the scientific basis that explains why this simple but important vitamin possesses such a wide range of positive biological activities.